VD_FINDINFO Décision / 2014 / 928 vom 22. Oktober 2014 - VD Tribunal cantonal (2014)
PARTIE À LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL | 105 al. 1 let. f CPP (CH), 105 al. 2 CPP (CH), 135 al. 4 let. b CPP (CH)